The regulatory role of exosomes in venous thromboembolism - Ye, Sheng-Lin; Li, Wen-Dong; Li, Wei-Xiao; Xiao, Lun; Ran, Feng; Chen, Meng-Meng; Li, Xiao-Qiang; Sun, Li-Li (Frontiers in Cell and Developmental Biology, 2022)
Exosomes are nanoscale endocytic vesicles, 30-150nm in diameter, secreted by most cells. They mainly originate from multivesicular bodies formed by intracellular invagination of lysosomal microparticles, and released into the extracellular matrix after fusion of multivesicular bodies with cell membrane. Studies have shown that exosomes contain a variety of active molecules, such as proteins, lipids and RNAs (such as mRNA, miRNA, lncRNA, circRNA, etc.), which regulate the behavior of recipient cells and serve as circulating biomarkers of diseases, including thrombosis. Therefore, exosome research is important for the diagnosis, treatment, therapeutic monitoring, and prognosis of thrombosis in that it can reveal the counts, surface marker expression, protein, and miRNA cargo involved. Recent studies have shown that exosomes can be used as therapeutic vectors for tissue regeneration and as alternative vectors for drug delivery. In this review, we summarize the physiological and biochemical characteristics, isolation, and identification of exosomes. Moreover, we focus on the role of exosomes in thrombosis, specifically venous thromboembolism, and their potential clinical applications, including as biomarkers and therapeutic vectors for thrombosis.